2017
DOI: 10.1038/ijir.2017.7
|View full text |Cite
|
Sign up to set email alerts
|

Association between periodontal disease and polycystic ovary syndrome: a systematic review

Abstract: The purpose of the present study was to review systematically the association between periodontal diseases (PDs) and polycystic ovary syndrome (PCOS). To address the focused question, 'Is there a relationship between PD and PCOS?' indexed databases were searched up to October 2016 without time or language restrictions using different combinations of the following key words: PCOS, ovarian cysts, PD, periodontitis, gingival diseases and gingivitis. Letters to the Editor, commentaries, historic reviews, case-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
2
27
0
1
Order By: Relevance
“…Our study, unlike other studies, revealed that PD, one of the periodontal health parameters, started to differentiate even though the cases were of early reproductive age, where periodontal diseases were rarely detected. Besides, as cases in the early reproductive stage were exposed to the hyperandrogenic and inflammatory environment of PCOS for a shorter period of time, deterioration in all periodontal findings may not have begun completely yet . Also, our study consisted of women who were recently diagnosed and had not received any hormonal or infertility treatment previously.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study, unlike other studies, revealed that PD, one of the periodontal health parameters, started to differentiate even though the cases were of early reproductive age, where periodontal diseases were rarely detected. Besides, as cases in the early reproductive stage were exposed to the hyperandrogenic and inflammatory environment of PCOS for a shorter period of time, deterioration in all periodontal findings may not have begun completely yet . Also, our study consisted of women who were recently diagnosed and had not received any hormonal or infertility treatment previously.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the association of periodontal diseases with PCOS has been under the spotlight in reproductive endocrinology and periodontology due to its association with inflammation and long‐term metabolic consequences . Previous studies claimed the increased risk of periodontal disease in PCOS . Although the underlying biological causes are unclear, hyperandrogenic environment induced by chronic anovulation in PCOS causes structural changes in the gingiva, increasing the risk of periodontal diseases by enabling bacteria to colonize more readily in the gum tissue .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations